Análisis de la rentabilidad de las empresas camaroneras del cantón santa rosa ante la pandemia covid-19. - Ortega Castillo, Dayana Carolina; Paltan Saca, Leidy Jacqueline (Universidad Técnica de Machala, 2022)
The shrimp sector has had to face a serious economic crisis at the origin of the covid-19 health emergency due to the restrictions and the paralysis caused by it, in such a way that this research aims to analyze the profitability of the shrimp companies in the canton Santa Rosa in the face of the covid-19 pandemic. It is worth mentioning that to support this research, reliable sources were used, as well as the use of the descriptive methodology in addition to attributing the quantitative and qualitative methods that served to corroborate the events that were occurring during the course of the pandemic as well, with the review of relevant information from reliable pages, it was possible to detect data collection mechanisms, including ideas that served in carrying out the analysis of shrimp exports in monetary figures with respect to the 2019-2020 period and thus be able to make an explicit conclusion.
El sector camaronero se ha tenido que enfrentar a una grave crisis económica a origen de la emergencia sanitaria covid-19 a causa de las restricciones y la paralización por la misma, de tal manera que esta investigación pretende analizar la rentabilidad de las empresas camaroneras del cantón Santa Rosa ante la pandemia covid-19. Cabe mencionar que para respaldar esta investigación se valió de fuentes fidedignas, así también se hizo uso de la metodología descriptiva además de atribuir los métodos cuantitativos y cualitativos que sirvieron para corroborar los hechos que iban ocurriendo en el transcurso de la pandemia asimismo, con la revisión de información relevante de páginas confiables se pudo detectar mecanismos de recolección de datos, incluso ideas que sirvieron en la realización del análisis de las exportaciones del camarón en cifras monetarias con respecto al periodo 2019-2020 y con ello poder realizar una conclusión explicita.
Keywords: EMPRESAS CAMARONERAS; COVID-19; EXPORTACIONES